Predicting order and timing of new product moves: the role of top management in corporate entrepreneurship - Srivastava, Abhishek; Lee, Hun (Journal of Business Venturing, 2005)
In this study, we focused on new product move as a form of corporate entrepreneurial activity. We developed hypotheses relating the characteristics of the top management team (TMT) to the order and timing of new product moves made by firms. We analyzed 223 new product introduction moves from the personal computer, long distance telecommunication, and brewing industries from the period of 1975–1990. We found that firms with larger TMTs were more likely to be first movers. The hypothesis that firms with larger TMTs are more likely to respond quickly to new product moves received marginal support. The hypothesis that TMTs more heterogeneous in terms of organizational tenure of executives are more likely to be first movers as well as earlier in the order of new product moves received marginal support. We found contradictory results with TMT organizational tenure and TMT educational background heterogeneity as predictors of order and timing of new product moves. Subsequently, we conducted industry-wise analysis that revealed important differences in this new product entrepreneurial activity across the three industries.